Sequence of Changes in Maize Responding to Soil Water Deficit and Related Critical Thresholds - Ma, Xueyan; He, Qijin; Zhou, Guangsheng (Frontiers in Plant Science, 2018)
The sequence of changes in crop responding to soil water deficit and related critical thresholds are essential for better drought damage classification and drought monitoring indicators. This study was aimed to investigate the critical thresholds of maize growth and physiological characteristics responding to changing soil water and to reveal the sequence of changes in maize responding to soil water deficit both in seedling and jointing stages based on two-year’s maize field experiment responding to 6 initial soil water statuses conducted in 2013 and 2014. Normal distribution tolerance limits were newly adopted to identify critical thresholds of maize growth and physiological characteristics to a wide range of soil water status. The results showed that in both stages maize growth characteristics related to plant water status (stem moisture content and leaf moisture content), leaf gas exchange (net photosynthetic rate, transpiration rate, and stomatal conductance), and leaf area were sensitive to soil water deficit, while biomass-related characteristics were less sensitive. Under the concurrent weather conditions and agronomic managements, the critical soil water thresholds in terms of relative soil moisture of 0-30cm depth (RSM) of maize stem moisture content, leaf moisture content, net photosynthetic rate, transpiration rate, stomatal conductance, and leaf area were 72%, 65%, 62%, 60%, 58%, and 46%, respectively in seedling stage, and 64%, 64%, 51%, 53%, 48%, and 46%, respectively in jointing stage. It indicated that there is a sequence of changes in maize responding to soil water deficit, i.e., their response sequences as soil water deficit intensified: stem moisture content ≥ leaf moisture content > leaf gas exchange > leaf area in both stages. This sequence of changes in maize responding to soil water deficit and related critical thresholds may be better indicators of damage classification and drought monitoring.